2016
DOI: 10.1016/j.poly.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of and catalytic nitrile hydration by a cationic tris(μ-hydroxo)diruthenium(II) complex having PMe3 ligands

Abstract: COD = cyclooctadiene (C8H12), COT = cyclooctatriene (C8H12), Cp* = pentamethylcyclopentadienyl (C5Me5-). DMPE = 1,2-bis(dimethylphosphino)ethane (Me2PC2H4PMe2), DEPE = 1,2bis(diethylphosphino)ethane (Et2PC2H4PEt2). KEYWORDS. CO Bond activation, Tris(hydroxo)diruthenium(II), Hydration of nitriles DEDICATION. This article celebrates Martin A. Bennett's 80 th birthday and numerous path breaking contributions to organometallic chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Aromatic nitriles have been mainly used in a ratio of about 2:1 with respect to aliphatic ones (Table S1). The reactions have been in an overwhelming preponderance performed in water as the solvent and, to a lesser extent, in alcohols, ethers, or their mixtures with water . Although complexes of metals of groups 6 , and 8–11 ,,,,,, have proven to be active for nitrile hydration reactions, more than half of the reported catalysts are ruthenium compounds, ,,− ,,,,,, and the vast majority of them bear specific ligands that enhance the solubility of the complex in water by means of the formation of hydrogen bonds with solvent molecules. ,,,,,,,,, The improvement of catalysts and reaction conditions have mainly been based on empirical data obtained from trial-and-error methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aromatic nitriles have been mainly used in a ratio of about 2:1 with respect to aliphatic ones (Table S1). The reactions have been in an overwhelming preponderance performed in water as the solvent and, to a lesser extent, in alcohols, ethers, or their mixtures with water . Although complexes of metals of groups 6 , and 8–11 ,,,,,, have proven to be active for nitrile hydration reactions, more than half of the reported catalysts are ruthenium compounds, ,,− ,,,,,, and the vast majority of them bear specific ligands that enhance the solubility of the complex in water by means of the formation of hydrogen bonds with solvent molecules. ,,,,,,,,, The improvement of catalysts and reaction conditions have mainly been based on empirical data obtained from trial-and-error methods.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions have been in an overwhelming preponderance performed in water as the solvent and, to a lesser extent, in alcohols, ethers, or their mixtures with water . Although complexes of metals of groups 6 , and 8–11 ,,,,,, have proven to be active for nitrile hydration reactions, more than half of the reported catalysts are ruthenium compounds, ,,− ,,,,,, and the vast majority of them bear specific ligands that enhance the solubility of the complex in water by means of the formation of hydrogen bonds with solvent molecules. ,,,,,,,,, The improvement of catalysts and reaction conditions have mainly been based on empirical data obtained from trial-and-error methods. Kinetic analysis of the reactions, , isolation of the reaction intermediates, ,, and a density functional theory (DFT) study of the catalysis ,, the three legs of the mechanistic investigationhave received scarce attention.…”
Section: Introductionmentioning
confidence: 99%
“… 9 In general, when acyclic vinyl ethers react with transition metal complexes, metal alkoxide species are the major product, concomitant with loss of alkene. 35 Recently, the Fujita group reported that [(η 5 -C 5 Me 5 Ir) 2 (μ-bis(dimethylphosphino)methane) (μ-H)][OTf] reacts with ethyl vinyl ether to give a dimeric Ir complex featuring a bridging vinyl ligand. 36 Conveniently, the vinyl complex 5 can be prepared in >93% yield via the reduction of ( acri PNP)NiCl with a magnesium powder in the presence of ethyl vinyl ether, see ESI.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 [(Ru(PMe3)3)2(µ-OH)3] + has been employed in E-selective alkyne dimerization reactions 14 and in nitrile hydration. 15 Ruthenium hydroxide intermediates have been implicated in other nitrile hydration reactions, 16 and in the dehydrogenation of methanol. 17 Several dimeric ruthenium complexes with bridging hydroxide ligands were prepared from the reaction of the corresponding chloride complexes with aqueous base, and were applied in the reduction of alkynes using alcohols as the hydrogen source (Scheme 3).…”
Section: Rutheniummentioning
confidence: 99%